The concentration of potentially toxic elements (PTEs) in human milk: A systematic review, meta-analysis, and health risk assessment - Aliasghar Neshat, - (Elsevier, 2023)
Human milk has an important role in infants' psychological and immunological development. In addition to providing vital substances, some environmental contaminants, such as potentially toxic elements (PTEs), can be transmitted by human breast milk to infants. However, some studies monitored PTEs concentration in human breast milk; no metanalysis was conducted to estimate the concentration of PTEs in human breast milk. Therefore, this review aimed to determine PTEs concentrations in human breast milk and consumption-related health effects worldwide via meta-analysis and health risk assessment. After searching among Scopus, Web of Science, and PubMed databases, 32 studies were included in this work. Based on the results, the rank order of PTEs was Fe (258.44 µg/kg) > Zn (205.16 µg/kg) > Cu (32.29 µg/kg) > Mn (4.30 µg/kg) > Cr (2.62 µg/kg) > Hg (0.44 µg/kg) > As (0.21 µg/kg) > Cd (0.16 µg/kg) > Pb (0.03 µg/kg). Moreover, Egypt, Pakistan, Brazil, Jordan, and Turkey for non-carcinogenic risk (n-CR) and Egypt, Jordan, Brazil, and Romania for carcinogenic risk (CR) have shown unsafe levels, respectively. Since the lactating mothers’ diet can directly affect their milk’s content, monitoring the feeding behavior (especially supplements taken during pregnancy) and the quality of foods is recommended.